(untitled) (The International Journal for Scientific Research, 2025)
This study aims to investigate the impact of the use of social networking sites on the formation of virtual identity and to identify the reasons why young people use an identity other than their real identity, in addition to revealing the effects of social networking sites on the personality model of its users and their social ties. It also explores the nature of the relationship between real and virtual identities.